Mongolia : Report on Observance of Standards and Codes-Fiscal Transparency Update. (IMF Staff Country Reports; Country Report, 2005)
This paper presents an update to the Report on the Observance of Standards and Codes (ROSC) on Fiscal Transparency for Mongolia. Since the publication of the ROSC in late 2001, Mongolia has made significant progress in enhancing transparency practices in the fiscal area. Actions have been taken under each of the four areas underlying the fiscal transparency code. A new Public Sector Management and Finance Law (PSMFL) was adopted in June 2002 to set the legal basis for public administration reforms, output budgeting, and accrual accounting.